THE IMPACT OF GAMIFICATION ON STUDENT MOTIVATION IN EFL CLASSROOMS: ENHANCING LEARNER ENGAGEMENT THROUGH DIGITAL PEDAGOGY (SCIENCE TIME JOURNAL, 2026)
This study investigates the effect of gamification on EFL students’ motivation, engagement, and vocabulary retention at Kokand State University. Using a quasi-experimental design, 30 first-year students were divided into experimental and control groups. The experimental group participated in gamified lessons using Kahoot, Quizizz, digital badges, and interactive tasks over six weeks. Data were collected through questionnaires, tests, observations, and interviews. Results showed that gamification significantly increased motivation, participation, and vocabulary learning, with a 28% improvement in the experimental group compared to 12% in the control group. The study concludes that gamification is an effective approach to enhancing both motivation and learning outcomes in EFL classrooms.